Unusual Airway Obstruction during General Anesthesia following Endotracheal Tube Cuff Herniation; A Case Report - Teymourian, Houman; Maddadi, Firoozeh; Khorasanizadeh, Shayesteh; Tizghadam, Atieh; Azizi Faresani, Hamidreza; Behnaz, Faranak; Ebrahimi Dehkordi, Masih (Novelty in Biomedicine, 2021)
Abstract Background: Airway management is always of great concern for anesthesiologists especially in the prone position. Utilizing an Armored endotracheal tube is considered to be safe in such patients. Cases Report: In this current case, we introduce a patient undergoing a wake-up test during spinal surgery who suffered from hypoventilation at the end of surgery. His condition improved only after extubation. After extubation, we confronted a herniated cuff that was not deflated, although we tried twice. We concluded that the patient’s respiratory effort against obstructed airway produced a negative pressure, which made the cuff herniated, resulting in airway obstruction. Moreover, the patient biting the tube during the wake-up test damaged the tube and cuff deflation pathway. Conclusion: It is important to consider cuff herniation as a cause of obstruction when other possible etiologies are ruled out.